Fostering Resilience in Adolescents at Risk: Study protocol for a cluster randomized controlled trial within the resilience school-based intervention - Llistosella, Maria; Torné, Clara; García-Ortiz, Mercedes; López-Hita, Griselda; Ortiz, Ramona; Herández-Montero, Laura; Guallart, Erika; Uña-Solbas, Estefanía; Miranda-Mendizabal, Andrea (Frontiers in Psychology, 2023)
Introduction: Resilience is considered of high relevance when developing interventions to cope with stressful situations. Schools are one of the key settings to promote resilience among adolescents. The purpose of this cluster randomized controlled trial is to assess the effectiveness of an intervention in adolescents at risk, aged 12-to-15 years old, to increase resilience and emotional regulation strategies. Methods: The recruitment period started in January 2022. Schools will be randomly allocated to control and intervention groups by an external researcher using computer-generated random numbers. The minimum sample size was estimated to be 70 participants per group. Primary health care nurses will carry out the intervention during the school period (January to June 2022). Students will follow a specific training consisting of six 55-minute sessions, for 6 weeks. Each session will consist of 5 minutes of mindfulness, followed by 45 minutes of the corresponding activity: introducing resilience, self-esteem, emotional regulation strategies, social skills, problem-solving, community resources, social and peer support, and 5 minutes to explain the activity to do at home. Data will be collected at baseline, 6 weeks, and 24 weeks after the intervention. The Child Youth Resilience Measure-32 scale will be used to assess the effectiveness of the intervention. This study received a grant in June 2021. Discussion: The intervention is intended to improve mental health through resilience. Different factors related to resilience will be promoted, such as self-esteem, emotional regulation, social and communication skills, problem-solving and peer support, among others. As it has been designed as a cluster-randomized school-based intervention, we will directly ameliorate the participation and engagement of the target population. With the present intervention, we expect to improve coping skills in adolescents by enhancing resilience capacities.